Automatic Car Control Prototype With Sound Application In Android Arduino Uno-Based: Automatic Car Control Prototype With Sound Application In Android Arduino Uno-Based - Muhammad Ade Dharamawan Nasution; Dedy Hartama; Fitri Anggraini; Rafiqa Dewi; Eva Desiana (Jurnal Mantik, 2020)
A car control device has been made with a voice application on an Android smartphone based on Arduino UNO. This tool uses HC-05 as a Bluetooth transmission media, Arduino Uno as the main controller and 2 DC motors as output. App Inventor is used to make a sound application on a smartphone, if the application receives a "forward" sound then both DC motors will advance. There are 5 voice commands that can be executed namely "forward", "backward", "right", "left" and "stop". From the results of trials that have been determined that this tool can control the car by giving voice commands that have been configured with a microcontroller with a considerable distance 3-5 meters.